RESEARCH ON VIBRATION FATIGUE LIFE OF VEHICLE EXHAUST SYSTEM UNDER TEMPERATURE FIELD DISTRIBUTION - SHU AiMei; WENG JianSheng; HAN Qiang; YU WenJie; SUN PengFei; LI JiWei (Jixie qiangdu)
Aiming at analyzing the influence of thermal load and mechanical load on the vibration characteristics and fatigue life of the exhaust system,the finite element model and modal test were conducted by modal analysis. The temperature field distribution of the exhaust system was obtained via CFD analysis. Finally,a frequency-domain called Dirlik was applied to analyze the vibration thermal fatigue life of this exhaust system. The results show that the structural modal frequency decreases under the temperature field distribution,and the fatigue life of the exhaust system considering temperature field distribution is 90. 8% lower than that not considering temperature distribution. Therefore,the temperature field distribution has significant effects on the fatigue life of the exhaust system,and it can’t be ignored during the development process.